2020
DOI: 10.4111/icu.20190313
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of partial nephrectomy—no ischemia vs. warm ischemia: Systematic review and meta-analysis

Abstract: This study aimed to determine the effectiveness and safety of partial nephrectomy (PN) without ischemia compared with PN with warm ischemia for reducing the deterioration in renal function in patients with cT1 renal tumors. Materials and Methods: We conducted a systematic review that included patients over 18 years of age who underwent PN with or without warm ischemia for cT1 renal tumors. The primary outcome was impaired renal function. A search strategy was performed in MEDLINE, EMBASE, LILACS, CENTRAL, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“… 5 , 6 The American Urological Association and European Association of Urology claim NSS as the operation of choice when feasible. 7 , 8 The average estimated blood loss of the laparoscopic approach was universally lower open approach, but warm ischemia time (WIT) was longer. 9 , 10 In a matched-pair study, the renal function was poorer in the laparoscopic PN cohort in the short-term after surgery.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 The American Urological Association and European Association of Urology claim NSS as the operation of choice when feasible. 7 , 8 The average estimated blood loss of the laparoscopic approach was universally lower open approach, but warm ischemia time (WIT) was longer. 9 , 10 In a matched-pair study, the renal function was poorer in the laparoscopic PN cohort in the short-term after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The ischemia time is an important issue for cases of PN, we used hot ischemia for all cases of PN with a mean time of 13.2±4.1 minutes which was slightly shorter than the time estimated by Mina-Riasco et al (16) which was 20.1±4.25 but this was a statistically insignificant difference.…”
Section: Discissionmentioning
confidence: 86%
“…The kidney is extremely sensitive to warm ischemia. Literature reported that the warm ischemia period should not exceed 30 min during partial nephrectomy (25)(26)(27). The energy-consuming metabolic activity of cortical cells reduces the consumption of oxygen and ATP, protects renal function, and prolongs the operation time.…”
Section: Discussionmentioning
confidence: 99%